(untitled) (Superficies y Vacío, 2024)
We thank the contributing authors for choosing Superficies y Vacío to communicate their research results, and quite as important, the selfless contribution of the peers who accepted to review the received manuscripts, helping to keep the high-quality of the articles that we publish. We hope for both communities to grow further in the times to come. This year, upon the suggestion of the ‘XVII International Conference on Surfaces, Materials, and Vacuum’s Organizing Committee, the Editorial Board extended a special invitation to the Conference contributors to send their results in a full manuscript to be considered for publication in Superficies y Vacío. In spite of the moderate response, we consider this has been a successful exercise, giving feedback from an editorial revision within 10 days from the Conference ending. I deeply appreciate the support from two Editorial Board colleagues, Cristo Manuel Yee Rendón and Martín Guadalupe Zapata Torres, with whom this initial process was completed satisfactorily. Nonetheless, to this day only one of thus received manuscripts has its peer review process complete. We are working to complete the review process for the remaining manuscripts under consideration within the first months of 2025. In Superficies y Vacío, we wish you all a Happy and Successful 2025! December 30th, 2024 Miguel Angel Santana-Aranda